Spinocerebellar Ataxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The onset below 15 years of age of autosomal dominant spinocerebellar ataxia (SCA) in 6 of 41 affected patients is reported from the Dept of Pediatrics, Baylor College of Medicine, Houston, TX.